Analysis of frailty change trajectories and its risk factors in patients with gastrointestinal tumor surgery: a prospective observational longitudinal study - Junli You; Xiaohong Lv; Yu Rong; Xuepiao Chen; Tianxiao Liu; Yubo Xie (World Journal of Surgical Oncology)
Abstract Background Frailty is a dynamic process, but its changes following surgery are unclear. This study aimed to investigate frailty change trajectories and their risk factors in older patients undergoing gastrointestinal tumor surgery. Methods The Frail Scale (FS) assessed frailty from preoperative to 180 days after surgery. The latent class analysis (LCA) was established to identify the most fitting latent class, and the risk factors of these change trajectories were analyzed. We also recorded and explored changes in FS components. Results 212 elderly patients (aged ≥ 60 years) scheduled for gastrointestinal tumor surgery under general anesthesia completed the study. The LCA identified four optimal trajectory groups. There are differences in gender, age, marriage, American Society of Anesthesiologists (ASA) classification, number of comorbidities, hemoglobin, Charlson comorbidity index (CCI), the six-minute walk test (6MWT), metabolic equivalent (MET), preoperative frailty status, and time to first ambulation among the four groups (P < 0.05). Comorbidities, MET, preoperative frailty, age, first time to ambulation, and 6WMT were independent factors influencing abnormal frailty trajectories. Overall, the FS components all changed 180 days after the surgery. Except for weight loss, the changes in the other components were related to the surgical site (P < 0.05). Conclusion Frailty is a dynamic process. Older patients with more comorbidities, low MET and 6WMT, preoperative frailty, and later time to ambulation are prone to remain in frailty or transition to it after surgery. Clinical attention and targeted rehabilitation should be provided to them.